Local Community Participation Seasonal Flood Disaster in Sidoarjo Regency, East Java - Idham; Mukhtar, Dzulkifli Bin (Universitas Bhayangkara Surabaya, 2024)
Irrigation in Sidoarjo Regency Drainage System Complex area of carrier channels to irrigation of the drainage (AFVOUR) in the display of water level regulators. High water surface in the channel causes slow flow of rain water catchment to a puddle. Conditions are exacerbated by backwater in the river channel in the area near the coast when the tide, causing floods to not be directly receding. Synergy has a combination of integration of various elements (for example, stakeholders) optimizing something better, legitimacy is considered to equalize perception hoping that actions are carried out in the desired action entity, appropriate according to value norms. Case Study Case data applies certain cases are generalized. Case study data is possible to be used to explore, examine comprehensiveness of a research object. Analysis of data using atlas, The weakness of the government's supervisor handles industrial waste into the River Peraul in Sidoarjo Regency, Urban Sprawl Social Impact Urbanization in big cities, controlling urbanization Increases development using the approach to touch the needs of the community needed Village, equity, spread of village remote development, the level of participation and understanding of the community provides feedback related to the concept of handling routine flood disasters every year. Seasonal flood disaster control in Sidoarjo Regency by involving local communities is an important approach by direct supervision by local communities, counseling on good water management practices, emergency response training, community based infrastructure development, coordinating between the government, local communities, form of concrete participation Local community in Sidoarjo Regency.